Boys like you - Stone, Juliana (Sourcebooks Fire, 2014)
When Monroe Blackwell, who is spending the summer at her grandmother's Louisiana bed-and-breakfast, meets Nathan Everets, who has a court-appointed job there, they share, and begin to recover from, their respective feelings of loss and guilt.